Corrigendum to “Diet and resource partitioning of juveniles of the scalloped hammerhead scalloped hammerhead and the blacktip Carcharhinus limbatus sharks co-occurring in Southern Gabon” [Region. Stud. Marine Sci. 100 (2026) 105199] - Youri Ivann Mvomo Minko; Lucien Besnard; Oumar Sadio; Jean-Daniel Mbega; Stéphan Ntie; Gaël Le Croizier; Jean-Marie Munaron; Gauthier Schaal; François Le Loc'h (Regional Studies in Marine Science, 2026)

Diet and resource partitioning of juveniles of the scalloped hammerhead scalloped hammerhead and the blacktip Carcharhinus limbatus sharks co-occurring in Southern Gabon - Youri Ivann Mvomo Minko; Lucien Besnard; Oumar Sadio; Jean-Daniel Mbega; Stéphan Ntie; Gaël Le Croizier; Jean-Marie Munaron; Gauthier Schaal; François Le Loc’h (Regional Studies in Marine Science, 2026)

A baseline for biodiversity: spatio-temporal variability of fish assemblages in the pristine and little-known Iguela Lagoon, Gabon - Nestor Ngoua Aba’a; Jean-Daniel Mbega; Oumar Sadio; Jean-Hervé Mve Beh; Jean-Félicien Liwouwou; Hans Kevin Mipounga; Frida Ben Rais Lasram; François Le Loc’h (Estuarine, Coastal and Shelf Science, 2025)

Underwater soundscape analysis reveals fish assemblage contrasts between protected and exploited areas in an African mangrove delta - Timothée Brochier; Oumar Sadio; Mamadou Diop; Frédéric Bertucci; Caouis Kammegne; Théophile Bayet; Balbine Olive MBoua Etoga; Hoover Esteban Pantoja Sanchez; Alassane Bah; Yann Tremblay (Biological Conservation, 2025)

Persistent organic pollutants and trace metals in selected marine organisms from the Akanda National Park, Gabon (Central Africa) - Fany Sardenne; François Le Loc'h; Nathalie Bodin; Jean-Hervé Mve-Beh; Jean-Marie Munaron; Jean-Daniel Mbega; Aimé Roger Nzigou; Oumar Sadio; Hélène Budzinski; Christophe Leboulanger (Marine Pollution Bulletin, 2024)

Lipid-correction models for δ13C values across small pelagic fishes (Clupeiformes) from the Atlantic Ocean - Fany Sardenne; Thomas Raynon; Jean-Marie Munaron; Carl D. van der Lingen; Oumar Sadio; Khady Diop; Pablo Brosset; Christophe Lebigre; Philippe Soudant; Marie Vagner; Laure Pecquerie (Marine Environmental Research, 2023)

Spatial and temporal structure of the fish assemblage in Akanda National Park (Gabon), an equatorial mangrove estuary - Jean Hervé Mve Beh; Oumar Sadio; Jean Daniel Mbega; Ghislain Tchinga; Flore Tsinga; Christophe Leboulanger; Ben Rais Lasram Frida; Tito de Morais Luis; François Le Loc’h (Regional Studies in Marine Science, 2023)

Sr Isotope Ratios (87Sr/86Sr) in Water and Fish Otoliths as Estuarine Salinity Tracers: Case Studies from Three NW African Rivers - Sebastian N. Höpker; Henry C. Wu; Friedrich Lucassen; Oumar Sadio; Timothée Brochier; Ishmael Y. Nuworkpor; Simone A. Kasemann; Peter Merschel; Hildegard Westphal (Estuaries and Coasts, 2022)
Variations of strontium isotope ratios ( 87 Sr/ 86 Sr) in river systems are increasingly utilised to geochemically trace origin and movement patterns of migratory fish species. Accretionary calcified structures, such as otoliths, preserve 87 Sr/ 86 Sr signatures of the surrounding water during a fish’s lifetime. In this study, we present 87 Sr/ 86 Sr measurements of water samples and catfish otoliths collected in the estuaries of the Sine-Saloum (Senegal), the Gambia River (The Gambia), and the Volta River (Ghana) to assess their systematics and relationships with salinity. The three rivers possess distinct hydrological properties resulting in variable degrees of correlations between 87 Sr/ 86 Sr and salinity. The Gambia River ( 87 Sr/ 86 Sr of ~ 0.71209) proved exceptionally preconditioned for the approach due to well-defined geochemical end-members, allowing for quantitative estimates of salinity based on otolith 87 Sr/ 86 Sr measurements. The Volta River (~ 0.71392) presents a more complex case due the possible influence of multiple water sources to the main channel, while the inverse salinity gradient and excessive evaporation in the Sine-Saloum estuary (~0.70915) impede any significant correlations between 87 Sr/ 86 Sr and salinity. Bulk otolith 87 Sr/ 86 Sr values in the Gambia River and Volta River clearly depicted a mixed influence of seawater and riverine compositions, strongly encouraging the application of this approach for geochemical fingerprinting of critical NW African species.

Biology and ecology of sea catfish (Ariidae) of estuarine, lagoon and coastal ecosystems in West Africa - Monique Simier; Olaloudé Judicaël Franck Osse; Oumar Sadio; Jean‐Marc Ecoutin (Journal of Fish Biology, 2021)
The family Ariidae, sea catfish of the order Siluriformes, is widely distributed throughout the world, particularly in tropical and subtropical areas. The three species of Ariidae found on the coasts and estuaries of West Africa are the smoothmouth catfish Carlarius heudelotii (Valenciennes 1840), the rough‐head catfish Carlarius latiscutatus (Günther 1864) and the Guinean sea catfish Carlarius parkii (Günther 1864). They have been increasingly exploited by artisanal and industrial coastal fisheries in recent decades, but there is still little information available on their ecology and biology. The aim of this study was to deepen our knowledge of these three West African Ariidae species based on a dataset collected between 1980 and 2013 during experimental fishing programmes. They were carried out in Mauritania in the Banc d'Arguin National Park, in Senegal in the Sine Saloum estuary including the Bamboung Marine Protected Area (MPA), in The Gambia in the Gambia estuary, in Guinea‐Bissau in the Urok Islands MPA in the Bijagos archipelago, in Guinea in the Fatala estuary and Dangara inlet, and in Côte d'Ivoire in the Ebrié Lagoon. C. latiscutatus accounted for 65%, C. parkii for 29% and C. heudelotii for 6% of total number of Ariidae sampled. C. latiscutatus was abundant in the Sine Saloum and Gambia estuaries as well as in Guinea and Guinea‐Bissau and was the only species present in the Ebrié Lagoon. C. parkii was in the majority in Mauritania. The three species were recorded in a salinity range of 0 to 50, a temperature range of 19 to 34°C, in areas 1.7 to 15 m depth, and transparency ranging from 0.1 to 4 m (Secchi disk depth). C. heudelotii was present in less saline (25 vs . 32–34), less warm (27 vs . 29°C) and less transparent (0.8 m vs . 1.6 m) waters than the two other species. The maximum sizes (453 mm, 614 mm and 525 mm for, respectively, C. heudelotii , C. latiscutatus and C. parkii ) were comparable to those recorded at sea. Length–weight relationships calculated for each species showed b coefficients greater than 3. Sex ratios were always in favour of females. The number of mature individuals and their smallest size at maturity were calculated per species, sex and study area. A size of 27–28 cm at first maturity was estimated for females of C. latiscutatus . A few dozen records made it possible to describe fecundity and cases of oral incubation by females. The diet of the three species was composed of crustaceans, fish and molluscs, confirming their classification as generalist predators. Thanks to their high environmental tolerance, these sea catfish populations are able to occupy both the continental shelf and adjacent estuaries throughout their life cycle, with the exception of spawning, which generally takes place at sea.

The leguminous trees Vachellia seyal (Del.) and Prosopis juliflora (Swartz) DC and their association with rhizobial strains from the root-influence zone of the grass Sporobolus robustus Kunth - Fatoumata Fall; Christine Le Roux; Amadou Mustapha Bâ; Dioumacor Fall; Niokhor Bakhoum; Mathieu Ndigue Faye; Oumar Sadio; Diegane Diouf (Symbiosis, 2021)

Fine-scale vertical structure of sound-scattering layers over an east border upwelling system and its relationship to pelagic habitat characteristics - Ndague Diogoul; Patrice Brehmer; Yannick Perrot; Maik Tiedemann; Abou Thiam; Salaheddine El Ayoubi; Anne Mouget; Chloé Migayrou; Oumar Sadio; Abdoulaye Sarré (Ocean Science, 2020)
Understanding the relationship between sound-scattering layers (SSLs) and pelagic habitat characteristics is a substantial step to apprehend ecosystem dynamics. SSLs are detected on echo sounders representing aggregated marine pelagic organisms. In this study, SSL characteristics of zooplankton and micronekton were identified during an upwelling event in two contrasting areas of the Senegalese continental shelf. Here a cold upwelling-influenced inshore area was sharply separated by a strong thermal boundary from a deeper, warmer, stratified offshore area. Mean SSL thickness and SSL vertical depth increased with the shelf depth. The thickest and deepest SSLs were observed in the offshore part of the shelf. Hence, zooplankton and micronekton seem to occur more frequently in stratified water conditions rather than in fresh upwelled water. Diel vertical and horizontal migrations of SSLs were observed in the study area. Diel period and physicochemical water characteristics influenced SSL depth and SSL thickness. Although chlorophyll-a concentration insignificantly affected SSL characteristics, the peak of chlorophyll a was always located above or in the middle of the SSLs, regularly matching with the peak of SSL biomass. Such observations indicate trophic relationships, suggesting SSLs to be mainly composed of phytoplanktivorous zooplankton and micronekton. Despite local hypoxia, below 30 m depth, distribution patterns of SSLs indicate no vertical migration boundary. The results increase the understanding of the spatial organization of mid-trophic species and migration patterns of zooplankton and micronekton, and they will also improve dispersal models for organisms in upwelling regions.

Ectomycorrhizal fungal communities of Coccoloba uvifera (L.) L. mature trees and seedlings in the neotropical coastal forests of Guadeloupe (Lesser Antilles) - Seynabou Séne; Raymond Avril; Clémence Chaintreuil; Alexandre Geoffroy; Cheikh Ndiaye; Abdala Gamby Diédhiou; Oumar Sadio; Régis Courtecuisse; Samba Ndao Sylla; Marc-André Selosse; Amadou Bâ (Mycorrhiza, 2015)